2023
DOI: 10.2147/ccid.s423177
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Trichoscopic Features and Serum Hormone Levels and Vitamin D Concentration in Patients with Androgenetic Alopecia in Eastern China: A Cross-Sectional Study

Qitao Chen,
Qiuwei Tao,
Qilin Zhu
et al.

Abstract: Purpose Androgenetic alopecia (AGA) is a common dermatological condition, with reported associations between serum vitamin D and sex hormone levels. However, the relationship between these factors and the severity of hair loss remains unclear. Patients and Methods Our cross-sectional study included 310 AGA patients who visited the dermatology clinic and underwent trichoscopy examinations throughout 2021. We collected data on serum sex hormones and 25(OH)D levels during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In humans, the role of SHGB is to protect against excess endogenous and exogenic steroids by combining with them [40]. Among female patients, Chen et al found that low-serum SHGB correlated negatively with AGA severity [41]. Taken together with our observation, this seems to confirm SHGB's crucial involvement in the presentation of AGA in women.…”
Section: Discussionsupporting
confidence: 87%
“…In humans, the role of SHGB is to protect against excess endogenous and exogenic steroids by combining with them [40]. Among female patients, Chen et al found that low-serum SHGB correlated negatively with AGA severity [41]. Taken together with our observation, this seems to confirm SHGB's crucial involvement in the presentation of AGA in women.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, AGA severity in women is negatively correlated with serum SHBG levels, which is explained by the fact that higher SHBG concentrations bind more testosterone, lowering its free and active fraction. Consequently, this decreases the negative impact of T on hair growth [ 33 ]. For this reason, total T measurement should be performed only in line with the SHBG test, which helps estimate the amount of free testosterone.…”
Section: Androgensmentioning
confidence: 99%